Do we need care thinning in young pine stands in their typical habitats? - N. M. Debkov (Сибирский лесной журнал, 2020)
Thinning is the main activity in the system of sustainable forest management. They define target indicators, which will have forest stands by the final cuttings. Scots pine Pinus sylvestris L. is the most widespread of economically valuable species. The aim of the work was an experimental verification of the probability of a species succession in typical pine habitats of the southern taiga of Western Siberia. The experimental area is located in the Timiryazevskiy forestry unit of the Tomsk Oblast, where green-mossy pine forests were cut down in 1999–2001. In 2010, thinning was carried out on young stands on an area of about 45 hectares. The thinning was carried out with a cutting of unwanted trees with strips of 5 m wide, i. e. cutting intensity was 50 %. As a result of studies, it was found that in the control plots, mixed stands with a share of scots pine about 40 % were formed. Aspen predominates in the stand composition, which is almost completely affected by rot of the trunk (90–100 %). Scots pine is much behind growth in aspen (2 times). The radial growth of trunk also indicates the suppression of the Scots pine. The two tier of stands is formed in the strip with thinning, where the upper tier is occupied by Scots pine, and the subordinate is aspen. The important stage in the creation of a new forest generation is the settlement dynamics of the felling area. For Scots pine, the pulsed nature of regeneration is confirmed – over a short period of time (3–4 years). Deciduous trees have a longer reforestation period (6–7 years). The increase in height in the strip with thinning turned out to be significantly higher than in the control plots (40–50 cm versus 20–30 cm). The developed system of felling, which consists in carrying out the first intake of non-commercial thinning at the age of 6–7 years old Scots pine and the second intake of thinning at 10–11 years, ensures the formation of Scots pine young stands.